PENGGUNAAN BAHASA HUKUM INDONESIA DALAM PERATURAN DAERAH KOTA KUPANG (Studi Penggunaan Bahasa Hukum dalam Peraturan Daerah Kota Kupang Nomor 2 Tahun 2015 Tentang Pengarusutamaan Gender) - Jenny Ermalinda (CV. Multi Kreasi Media, 2023)
In 2015, the Kupang City Government together with the Kupang City Regional People's Representative Council promulgated twelve Perda. Even though it has been promulgated through a juridical mechanism, it turns out that there are still regional regulations which give rise to various interpretations due to the use of legal language that is incorrect, inaccurate and unclear. Therefore, the problem of this writing is whether the structure of the legal language of the Kupang City Regional Regulation is in accordance with the rules of good legal language and what legal meaning underlies the thoughts of the Kupang City Regional Regulation. The results of the study show that the formation of the Regional Regulation of the City of Kupang Number 2 of 2015 concerning Gender Mainstreaming does not use a good and correct structure of Indonesian legal language, because in the regional regulation found the language of norms that are not properly organized, and ethics and logic that are not aligned. However, in terms of the use of Indonesian legal language which means the Kupang City Regional Regulation Number 2 of 2015 has used Indonesian legal language which means/is in the nature of orders, choices, prohibitions, and freedoms.